Study on Ecological Flow in Hejiang River - ZHANG Pan; KONG Lan; ZHANG Fangxiu; WANG Ming (Renmin Zhujiang)
Based on the series of hydrological data from the controlling hydrological station of Xindu and Gulan in the mainstream of Hejiang River,this paper uses hydrological methods to study ecological flow in Hejiang River.After analyzing and comparing the results of different calculation methods,the calculation results of the 90% guarantee rate of the driest month average method and the annual exhibition calculation method are selected as the ecological base flow and the annual volume of the basic ecological flow in the river.The ecological base flow of Xindu Station and Gulan Station are 26.5 and 34.6 m3/s,and the annual volumes are 58.8 and 87.0 m3/s;the calculation result of the frequency curve method is taken as the target ecological flow in the river,and the annual volume of Xindu Station and Gulan Station is 83.9 and 121.0 m3/s.The research results aim to provide theoretical support for the management and protection of Hejiang River in the future and serve as a reference for improving the rational allocation of regional water resources.